Silver nanoparticle-loaded microgel-based etalons for H2O2 sensing. Issue 28 (24th April 2018) - Shu, Tong; Shen, Qiming; Wan, Yu; Zhang, Wei; Su, Lei; Zhang, Xueji; Serpe, Michael J.
Abstract : Silver nanoparticle (AgNP)-loaded poly( N -isopropylacrylamide)- co -acrylic acid (pNIPAm- co -AAc)-based microgels were generated and used to make etalons. The etalons were shown to exhibit optical properties that depended on the concentration of H2 O2 in solution. Abstract : Silver nanoparticles (AgNPs) were generated inside the network structure of poly( N -isopropylacrylamide)- co -acrylic acid (pNIPAm- co -AAc) microgels that were sandwiched between two thin Au layers (15 nm) of an etalon. This was done by introducing Ag + to the etalons composed of deprotonated microgels, followed by its subsequent reduction with NaBH4 . The resultant microgels were collected and then characterized by transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS), verifying the loading of AgNPs with relatively uniform diameter (5–7 nm) within the microgels. Furthermore, the optical properties of the resultant etalons and their response to H2 O2 were evaluated by reflectance spectroscopy. Specifically, upon the addition of H2 O2, the AgNP-loaded etalons exhibited both a red shift in the position of the reflectance peaks and an increase in reflected wavelength intensity. We hypothesize that the dual signal response of the devices was a result of oxidative decomposition of the AgNPs, enabling the microgels to swell and for more light to be reflected (due to the loss of the light absorbing AgNPs). Finally, we showed that the AgNPs could be regenerated in the used etalons multiple times without a loss in performance. This work provides a cost-effective means to detect H2 O2, which could be modified to sense a variety of other species of physiological and environmental importance through rationally loading other functional nanomaterials.